Intertextuality in the Poetry of Mudar Al-Alusi - Hussein, Reham Mansour; Matlab, Abdul Rahman Khalaf (Journal of Cultural Analysis and Social Change, 2025)
From our study of poetic themes and poetic intertextuality in Al-Alusi's work, we conclude that the nature of poetic language and poetic intertextuality employed by the poet Mudar Al-Alusi in his various poems left a clear impression on the listener due to his ability to combine emotional depth on the one hand and psychological contemplation on the other. This was reflected in his themes, which were characterised by their humanistic nature through the lexical repertoire that appeared in his poems (homeland, elegy, religion, praise, etc.), while the poetry of his vocabulary was distinguished by its oscillation between the use of heritage mixed with everyday words and the language of the era associated with the lives of ordinary people. This indicates the religious environment in which he was raised and his attachment to his rich heritage, which we see in the poetic intertextuality of his poems, where religious heritage was a source of inspiration for the poet. We find that religious texts quoted from the Holy Quran and the Hadith are intertwined with most of his poems. Literary intertextuality also played a role in his poems, which he embellished with proverbs and literary texts that he used as a starting point for his creativity.